2017
DOI: 10.1007/s10584-017-2030-0
|View full text |Cite
|
Sign up to set email alerts
|

Attributing extreme fire risk in Western Canada to human emissions

Abstract: Canada is expected to see an increase in fire risk under future climate projections. Large fires, such as that near Fort McMurray, Alberta in 2016, can be devastating to the communities affected. Understanding the role of human emissions in the occurrence of such extreme fire events can lend insight into how these events might change in the future. An event attribution framework is used to quantify the influence of anthropogenic forcings on extreme fire risk in the current climate of a western Canada region. F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
88
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 101 publications
(88 citation statements)
references
References 43 publications
0
88
0
Order By: Relevance
“…Fire weather Beer and Williams 1995;Flannigan et al 1998;Miller and Schlegel 2006;Moriondo et al 2006;Malevsky-Malevich et al 2008;Bedia et al 2015 Fire danger rating Flannigan andVan Wagner 1991;Bergeron and Flannigan 1995;Flannigan et al 2000;Amiro et al 2001;Williams et al 2001;Kochtubajda et al 2006;Pitman et al 2007;Liu et al 2010;Flannigan et al 2013;Wang et al 2015 Area burned Price and Rind 1994;Weber and Flannigan 1997;Flannigan et al 2005Flannigan et al , 2009aFlannigan et al , 2009bCary et al 2006;Podur and Wotton 2010;Wimberly and Liu 2014;Bedia et al 2015;Wu et al 2015 example, lower relative humidity, higher temperatures, and modified precipitation patterns (Flannigan and Van Wagner 1991;Flannigan et al 2000;Kochtubajda et al 2006). Research suggests that anthropogenic climate change has already increased the likelihood of extreme fire risk in western Canada by 1.5 to 6 times during the current decade (Kirchmeier-Young et al 2017). Anthropogenic climate change is also anticipated to affect fire season length (Wotton and Flannigan 1993;Flannigan et al 2013), with observed trends in keeping with predictions.…”
Section: Predicted Effectsmentioning
confidence: 99%
“…Fire weather Beer and Williams 1995;Flannigan et al 1998;Miller and Schlegel 2006;Moriondo et al 2006;Malevsky-Malevich et al 2008;Bedia et al 2015 Fire danger rating Flannigan andVan Wagner 1991;Bergeron and Flannigan 1995;Flannigan et al 2000;Amiro et al 2001;Williams et al 2001;Kochtubajda et al 2006;Pitman et al 2007;Liu et al 2010;Flannigan et al 2013;Wang et al 2015 Area burned Price and Rind 1994;Weber and Flannigan 1997;Flannigan et al 2005Flannigan et al , 2009aFlannigan et al , 2009bCary et al 2006;Podur and Wotton 2010;Wimberly and Liu 2014;Bedia et al 2015;Wu et al 2015 example, lower relative humidity, higher temperatures, and modified precipitation patterns (Flannigan and Van Wagner 1991;Flannigan et al 2000;Kochtubajda et al 2006). Research suggests that anthropogenic climate change has already increased the likelihood of extreme fire risk in western Canada by 1.5 to 6 times during the current decade (Kirchmeier-Young et al 2017). Anthropogenic climate change is also anticipated to affect fire season length (Wotton and Flannigan 1993;Flannigan et al 2013), with observed trends in keeping with predictions.…”
Section: Predicted Effectsmentioning
confidence: 99%
“…Joint attribution efforts for natural systems are more challenging than attribution of meteorological and climate variables to anthropogenic climate change (Rosenzweig et al, 2008), let alone coupled natural-human processes such as fire. As an alternative, a limited set of attribution studies that focus on atmospheric drivers and enablers of fire have been conducted but have often been limited geographically and methodologically (e.g., Gillett et al, 2004;Kirchmeier-Young et al, 2017;.…”
Section: Introductionmentioning
confidence: 99%
“…For example, in Alberta alone, wildfire impacts an average of ∼208,000 ha every year (2006–2015; Government of Alberta, 2017) with fires liberating large quantities of the C stored in peatlands across the province to the atmosphere (approximately 4.7 × 10 9 g of C released per year; Turetsky et al, ). With fire frequency expected to roughly double by the end of the century, from enhanced warming and longer fire seasons (Wotton & Flannigan, ; Flannigan, Stocks, Turetsky, & Wotton, ; Flannigan et al ., ; Kirchmeier‐Young, Zwiers, Gillet, & Cannon, ; Hanes, Wang, Jain, Parisien, & Little, ), as well as an increase in the number of large high‐intensity wildfires (Tymstra et al ., ), boreal peatlands may be vulnerable to changes in wildfire regime under a rapidly changing climate. Despite these increasing pressures, the impact of fire on DOC concentration, quality, and export across boreal peatlands is not always consistent, with studies showing an increase (McEachern, Prepas, Gibson, & Dinsmore, ), no change (Carignan, D'Arcy, & Lamontagne, ; Lamontagne, Carignan, D'Arcy, Prairie, & Paré, ; Marchand et al ., ), or decrease (Betts & Jones, ) in DOC concentration in surface waters.…”
Section: Introductionmentioning
confidence: 99%